HUBUNGAN TINGKAT PENGETAHUAN PRA ANESTESI DENGAN TINGKAT KECEMASAN PRA ANESTESI PADA PASIEN OPERASI ELEKTIF DI RUMAH SAKIT AMALIA BONTANG - Nuryanti; Joko Sapto Pramono; Abd.Kadir (Bajang Institute, 2024)
Background:Worry pre operation often linked with procedure anesthesia, so expert anesthesia is best suited to reduce worry patient with ensure effective communication _ between doctor and patient during visit inspection pre-anesthesia pressure blood and pulse patient. Effective communication _ during visit pre-anesthesia is also a factor important in reduce worry Purpose: to find out is There is connection between level knowledge pre anesthesia with level worry pre anesthesia at Amalia Bontang Hospital.Method:This research is study Cross Sectional with sample totaling 55 pre- anesthesia patients in the room maintenance 3rd floor with retrieval technique sample is Purposive sampling uses the Chi square test.Results: chi square test analysis results obtained p value = 0.000 ≤ 0.05 with can withdrawn conclusion There is significant relationship _ between level knowledge pre anesthesia with level worry pre anesthesia in patients operation electi at Amalia Bontang Hospital.